Hijrah Movement in Indonesia: Shifting Concept and Implementation in Religiosity - Hamudy, Nurul Annisa; Hamudy, Moh. Ilham A. (JSW (Jurnal Sosiologi Walisongo), 2020)
Hijrah is considered as a change in attitude and religious experience, from looseness to strictness. The phenomenon of hijrah shows the view that piety should be appeared in outward form. This research illustrates that hijrah is not always a role model of piety, but it can also be a spread of frozen ideology, depicting the commodification of religion, and is considered as discussing only á¸¥alÄl and á¸¥arÄm issues. Applying a qualitative approach, this study takes the data in litterer source both the religious text and media. The sources of data in media come from media statements related to the hijrah phenomenon. The research results show: first, hijrah is interesting for some Muslims because Islamic teachings are more practical, less philosophical and complicated. Second, the meaning of hijrah as its original meaning is not limited to aspects of existence; rather, the religious spirit is interpreted as a personal spiritual journey that will continue throughout human life. The shifting phenomenon on hijrah much influenced by media and social media wave that blow up the value of practicality, consumerism, and commodification of religion.